Rethinking Malaysia politics, extremism and education - Mohamad Tajuddin Haji Mohamad Rasdi 1962- (Strategic Information and Research Development Centre, 2020)
Rethinking Malaysia collects together the writings of Tajuddin Rasdi in a period of political change and turmoil in the aftermath of Malaysia's 14th General Election. A time of hope and renewal, as well as of increasing conservatism and extremism, Rethinking Malaysia features Tajuddin Rasdi⁰́₉s personal and honest musings about issues of religion, politics, and education in relation to Malaysia⁰́₉s ongoing project of nation-building. Reacting to events such as the anti-ICERD rally, the Zakir Naik controversy, the education reforms of the Pakatan Harapan government, and the worsening of relations between East and West Malaysia, Rethinking Malaysia is Tajuddin Rasdi's call for a process of nation-building which is inclusive of all races, religions and regions and which produces a meaningful Malaysian identity, as well as a call for all religions to work together to produce a more prosperous, just and inclusive nation for future generations.